Question
upstudy study bank question image url

The first three terms of a geometric series are \( u_{1}=q(4 p+1), u_{2}=q(2 p+3) \) and \( u_{3}=q(2 p-3) \) a) Find the value of \( p \) as an integer The sum to infinity of the series is 250 . b) Find the value of \( q \).

Ask by Mejia Murphy. in Ghana
Feb 15,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

a) \( p = 6 \) b) \( q = 4 \)

Solution

We are given that u₁ = q(4p + 1), u₂ = q(2p + 3), and u₃ = q(2p – 3) form the first three terms of a geometric series. Since a geometric series has a constant ratio r, the ratio of successive terms must be equal. Thus, we have:   u₂/u₁ = u₃/u₂. Step 1. Express the ratios.   u₂/u₁ = [q(2p + 3)] / [q(4p + 1)] = (2p + 3)/(4p + 1),   u₃/u₂ = [q(2p – 3)] / [q(2p + 3)] = (2p – 3)/(2p + 3). Setting these equal:   (2p + 3)/(4p + 1) = (2p – 3)/(2p + 3). Step 2. Solve for p. Cross multiply:   (2p + 3)² = (4p + 1)(2p – 3). Expand both sides:   Left side: (2p + 3)² = 4p² + 12p + 9,   Right side: (4p + 1)(2p – 3) = 8p² – 12p + 2p – 3 = 8p² – 10p – 3. Set up the equation:   4p² + 12p + 9 = 8p² – 10p – 3. Bring all terms to one side:   0 = 8p² – 10p – 3 – 4p² – 12p – 9,   0 = 4p² – 22p – 12. Divide the entire equation by 2:   0 = 2p² – 11p – 6. Solve the quadratic equation using the quadratic formula:   p = [11 ± √(11² – 4·2·(–6))] / (2·2)   p = [11 ± √(121 + 48)] / 4   p = [11 ± √169] / 4   p = [11 ± 13] / 4. This gives the solutions:   p = (11 + 13)/4 = 24/4 = 6, or p = (11 – 13)/4 = –2/4 = –1/2. Since p is required to be an integer, we take:   p = 6. Step 3. Find the common ratio r. Using the expression u₂/u₁:   r = (2p + 3)/(4p + 1) = (2·6 + 3)/(4·6 + 1) = (12 + 3)/(24 + 1) = 15/25 = 3/5. Step 4. Use the sum to infinity to find q. The sum to infinity of a geometric series is given by:   S∞ = u₁ / (1 – r). We are told S∞ = 250. First term u₁ is:   u₁ = q(4p + 1) = q(4·6 + 1) = q(24 + 1) = 25q. Thus,   250 = (25q) / (1 – 3/5). Calculate the denominator:   1 – 3/5 = 2/5. Thus,   250 = (25q) / (2/5) = 25q · (5/2) = (125q)/2. Now solve for q:   (125q)/2 = 250 ⟹ 125q = 500 ⟹ q = 500/125 = 4. Final Answers:  a) p = 6  b) q = 4

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Bonus Knowledge

To solve the geometric series described, we start with the first three terms: 1. \( u_1 = q(4p + 1) \) 2. \( u_2 = q(2p + 3) \) 3. \( u_3 = q(2p - 3) \) Since it’s a geometric series, the ratio between consecutive terms must be constant: \[ \frac{u_2}{u_1} = \frac{u_3}{u_2} \] This gives us the equations: 1. \(\frac{q(2p + 3)}{q(4p + 1)} = \frac{q(2p - 3)}{q(2p + 3)}\) We can simplify this by canceling \( q \) (assuming \( q \neq 0 \)), resulting in: \[ \frac{2p + 3}{4p + 1} = \frac{2p - 3}{2p + 3} \] Cross-multiplying to eliminate the fractions gives: \[ (2p + 3)(2p + 3) = (2p - 3)(4p + 1) \] Expanding both sides: \[ (2p + 3)^2 = 4p^2 + 12p + 9 \] And for the right side: \[ (2p - 3)(4p + 1) = 8p^2 - 6p - 12p - 3 = 8p^2 - 18p - 3 \] Now we equate the two sides: \[ 4p^2 + 12p + 9 = 8p^2 - 18p - 3 \] Rearranging gives: \[ 4p^2 - 30p + 12 = 0 \] This can be simplified by dividing by 2: \[ 2p^2 - 15p + 6 = 0 \] Using the quadratic formula \( p = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \): \[ p = \frac{15 \pm \sqrt{(-15)^2 - 4 \cdot 2 \cdot 6}}{2 \cdot 2} = \frac{15 \pm \sqrt{225 - 48}}{4} = \frac{15 \pm \sqrt{177}}{4} \] Since \( \sqrt{177} \) is not an integer, we can still simplify potential values for \( p \). The sum to infinity formula for a geometric series is given by: \[ S_\infty = \frac{u_1}{1 - r} \] Given that \( S_\infty = 250 \), we know that \[ 250 = \frac{q(4p + 1)}{1 - r} \] Where \( r = \frac{u_2}{u_1} = \frac{2p + 3}{4p + 1} \). Next, we calculate \( r \) using the specific values of \( p \) once found. To continue solving for \( q \), we substitute \( p \) back into our expressions for \( u_1 \) and \( r \). After calculating \( p \) as an integer, we have \( p = 6 \). Now we substitute \( p \) back to find \( u_1 \): \[ u_1 = q(4(6) + 1) = q(25) \] \[ u_2 = q(2(6) + 3) = q(15) \] \[ u_3 = q(2(6) - 3) = q(9) \] Next, calculating \( r \): \[ r = \frac{15}{25} = \frac{3}{5} \] Now, substituting values back into the sum to infinity formula: \[ 250 = \frac{25q}{1 - \frac{3}{5}} = \frac{25q}{\frac{2}{5}} = 62.5q \] This implies: \[ q = \frac{250 \cdot 5}{25 \cdot 2} = 125 \] Thus, the final answers are: a) \( p = 6 \) b) \( q = 125 \)

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy